Emergence, spread, and impact of high‐pathogenicity avian influenza H5 in wild birds and mammals of South America and Antarctica - Thijs Kuiken; Ralph Eric Thijl Vanstreels; Ashley Banyard; Lineke Begeman; Andrew C. Breed; Meagan Dewar; Ruben Fijn; Patricia Pereira Serafini; Marcela Uhart; Michelle Wille (Conservation Biology, 2026)
The currently circulating high‐pathogenicity avian influenza (HPAI) virus of the subtype H5 causes variable illness and death in wild and domestic birds and mammals, as well as in humans. This virus evolved from the Goose/Guangdong lineage of the HPAI H5 virus, which emerged in commercial poultry in China in 1996, spilled over into wild birds, and spread through Asia, Europe, Africa, and North America by 2021. Our objective was to summarize the spread and impact of the HPAI H5 virus in wild birds and mammals in South America, evaluate the risk of its spread and potential impact on Antarctic wildlife, and consider actions to manage the current and future HPAI outbreaks in wildlife. We obtained data on HPAI H5 virus detection and reported wildlife deaths from websites, newspaper articles, and scientific publications. The virus arrived in South America in October 2022. Thereafter, it spread widely and rapidly throughout the continent, where it infected at least 83 wild bird species and 11 wild mammal species and is estimated to have killed at least 667,000 wild birds and 52,000 wild mammals. The HPAI H5 virus spread to the Antarctic region by October 2023 and to mainland Antarctica by December 2023. This spread was associated with multiple mortality events in seabirds and marine mammals. The high spatial density of colonies of various Antarctic species of birds and mammals provides conditions for potentially devastating outbreaks with severe conservation implications. Ecosystem‐level impacts may follow, and affected populations may take decades to recover. Although little can be done to stop the virus spread in wildlife, it is important to continue targeted surveillance of wildlife populations for HPAI H5 virus incursion and assessment of the spread and impact of disease to inform adaptation of conservation plans and to help policy makers mitigate and prevent future HPAI outbreaks.

The first report of Listeria monocytogenes detected in pinnipeds - Johanna L. Baily; Gavin K. Paterson; Geoffrey Foster; Nicholas J. Davison; Lineke Begeman; Ailsa J. Hall; Mark P. Dagleish (Journal of Comparative Pathology, 2024)

Pathological findings in stranded harbor porpoises (Phocoena phocoena) with special focus on anthropogenic causes - Lonneke L. IJsseldijk; Mardik F. Leopold; Lineke Begeman; Marja J. L. Kik; Lidewij Wiersma; Maria Morell; Elisa L. Bravo Rebolledo; Thierry Jauniaux; Hans Heesterbeek; Andrea Gröne (Frontiers in Marine Science, 2022)
Humans impact natural systems at an unprecedented rate. The North Sea is one of the regions in the world with the highest levels of anthropogenic activity. Here, the harbor porpoise ( Phocoena phocoena ) is an abundant species and is often regarded as an ecosystem sentinel. A post-mortem surveillance program was established in the Netherlands aimed at increasing knowledge of the effects of human activities on harbor porpoises. In this study, we describe the pathological findings related to anthropogenic and natural causes of death categories in 612 harbor porpoises that stranded between 2008 and 2019, and assess their relations to age, sex, season, and location. The largest anthropogenic category was bycatch (17%), with mainly juveniles affected and peak periods in March and September–October. Other, infrequently diagnosed anthropogenic causes of death were trauma (4%), largely most likely due to ship collisions, and marine debris ingestion and entanglement (0.3%). The risk of dying from anthropogenic causes was highest for juveniles. Lesions compatible with noise-induced hearing loss were investigated in carcasses which were fresh enough to do so (n = 50), with lesions apparent in two porpoises. Non-direct human-induced threats included infectious diseases, which were by far the largest cause of death category (32%), and affected mainly adults. Also, gray seal ( Halichoerus grypus ) attacks were a frequently assigned cause of death category (24%). There were more acute predation cases in the earlier study years, while porpoises with lesions that suggested escape from gray seal attacks were diagnosed more recently, which could suggest that porpoises adapted to this threat. Our study contributes to understanding porpoise health in response to persisting, new, emerging, and cumulative threats. Building up such knowledge is crucial for conservation management of this protected species.

A novel cetacean adenovirus in stranded harbour porpoises from the North Sea: detection and molecular characterization - Steven J. van Beurden; Lonneke L. IJsseldijk; Marco W. G. van de Bildt; Lineke Begeman; James F. X. Wellehan; Thomas B. Waltzek; Geert de Vrieze; Andrea Gröne; Thijs Kuiken; M. Hélène Verheije; Judit J. Penzes (Archives of Virology, 2017)